Fe and O isotope composition of meteorite fusion crusts: Possible natural analogues to chondrule formation?. (12th February 2015) - Hezel, Dominik C.; Poole, Graeme M.; Hoyes, Jack; Coles, Barry J.; Unsworth, Catherine; Albrecht, Nina; Smith, Caroline; Rehkämper, Mark; Pack, Andreas; Genge, Matthew; Russell, Sara S.
Abstract Meteorite fusion crust formation is a brief event in a high‐temperature (2000–12, 000 K) and high‐pressure (2–5 MPa) regime. We studied fusion crusts and bulk samples of 10 ordinary chondrite falls and 10 ordinary chondrite finds. The fusion crusts show a typical layering and most contain vesicles. All fusion crusts are enriched in heavy Fe isotopes, with δ56Fe values up to +0.35‰ relative to the solar system mean. On average, the δ56Fe of fusion crusts from finds is +0.23‰, which is 0.08‰ higher than the average from falls (+0.15‰). Higher δ56Fe in fusion crusts of finds correlate with bulk chondrite enrichments in mobile elements such as Ba and Sr. The δ56Fe signature of meteorite fusion crusts was produced by two processes (1) evaporation during atmospheric entry and (2) terrestrial weathering. Fusion crusts have either the same or higher δ18O (0.9–1.5‰) than their host chondrites, and the same is true for Δ17O. The differences in bulk chondrite and fusion crust oxygen isotope composition are explained by exchange of oxygen between the molten surface of the meteorites with the atmosphere and weathering. Meteorite fusion crust formation is qualitatively similar to conditions of chondrule formation. Therefore, fusion crusts may, at least to some extent, serve as a natural analogue to chondrule formation processes. Meteorite fusion crust and chondrules exhibit a similar extent of Fe isotope fractionation, supporting the idea that the Fe isotope signature of chondrules was established in a high‐pressure environment that prevented large isotope fractionations. The exchange of O between a chondrule melt and an 16O‐poor nebula as the cause for the observed nonmass dependent O isotope compositions in chondrules is supported by the same process, although to a much lower extent, in meteorite fusion crusts.